Da justiça e das penas: sistema prisional e reformulação penitenciária no Ceará - Siqueira, Ítalo Barbosa Lima (2023)
The thesis aims to sociologically understand the reformulation of the political management of the prison system following the creation of the Secretariat of Penitentiary Administration of the State of Ceará (SAP), during the administrative reform of the second Camilo Santana government (2019 — 2022). The sociopolitical context locates the Ceará prison system in the dynamics of institutional changes to face the problems arising from the expansion of incarceration and its consequences in the daily lives of managers, technicians, penitentiary security agents, inmates, family members, inmates and their communities. In a more apparent way, the penitentiary reformulation was justified to neutralize the demanding and insurgent events of the prison population, portrayed as the action of “factions” operating in the state of Ceará, aiming to undermine the coordination of acts of instability in security inside and outside prisons. Through the doctrine of penitentiary intervention, the prison administration tried to demobilize the groups capable of gathering and organizing people in Ceará's prison units, through the training and strengthening of the criminal police trained to adopt a routine of strict control of the prison population through operational procedures for distributing suffering and punishment. Therefore, the emergence of factions within prison units precipitated strong pressure for changes in the management of the prison system and an attempt to collaborate with criminal justice. In this context, Ceará governors invested in expanding and improving the public security system and increasing repression and incarceration resources. The methodological approach is based on the analysis of documentary research on the political-bureaucratic context of state intervention in the prison system and fieldwork engaged with family members and social movements defending the human rights of the prison population, in addition to field research carried out around and inside Ceará prisons. Thus, the overflow of prisons in Ceará and its social effects on the daily lives of populations and communities in the Metropolitan Region of Fortaleza (RMF) can be seen, complemented by the social experience of family members of prisoners and the mobilizations of civil society for the fulfillment of human rights. in the prison system. As a result, the thesis analyzes the reformulation of the prison system towards the doctrine of penitentiary intervention, the center of the policy of disciplinary management of sentences, celebrated by the permanent rhetoric of police war against criminals.